Rethinking the ‘Western Tradition’ - Enslin, Penny; Horsthemke, Kai (My University, 2015)
In recent years, the ‘Western tradition’ has increasingly come under attack in anti-colonialist and postmodernist discourses. It is not difficult to sympathise with the concerns that underlie advocacy of historically marginalised traditions, and the West undoubtedly has a lot to answer for. Nonetheless, while arguing a qualified yes to the central question posed for this special issue, we question the assumption that the West can be neatly distinguished from alternative traditions of thought. We argue that there is fundamental implicit and explicit agreement across traditions about the most difficult of issues and on standards about how to reason about them and that the ‘West’ has demonstrably learned from within and without itself. But, we question the very viability under conditions of heightened globalisation and neo-colonialism of distinguishing between thought of the ‘West’ and thought outside the West. It is time to move beyond the reified assumptions that underlie the idea of ‘Western thought’, cast as an agent with a collective purpose.
Keywords: Indigenous knowledge – philosophy; Western knowledge systems -- blind spots and blank spots; Western knowledge systems – attacks on; Neo-colonialism – philosophy; Orientalism – philosophy